Struktur Naratif Kakawin Nirartha Prakreta : Kajian Bahasa, Sastra, Dan Budaya - Permana Putra, I Nyoman Dwiki (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Bali is one of the regions in Indonesia helping maintain the richness of the archipelago in the form of literary works, one of which is Old Javanese literary works which are still well preserved today. Old Javanese literary works are special and relatively old literary ones because most of the literary works are from the IX and XV centuries (Zoetmulder, 1985: 18-25). The method used is the library study method and manuscript reading, namely using the listening method. The listening method is a method used to obtain data by listening to language use. The term listening here is not only related to the use of language orally, but also in writing (Mashun, 2005:90). Heuristic and hermeneutic reading is also used and assisted by note-taking and translation techniques. Based on the corpus of Kakawin Nirartha Prakrĕta, it can be concluded that the storyline contains a life picture of good and bad behavior in life which in Hinduism is called Subha Asubha Karma. This proves the narrative unit about dharma teachings (dharmasastra) which dominates the story content of Kakawin Nirartha Prakrĕta. It can be concluded that before interpreting a kakawin text we must first know its structureThe narrative structure that builds Kakawin Nirartha Prakrĕtha includes Manggala